2016
DOI: 10.12659/msmbr.901909
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin1 (SIRT1) Regulates Tumor Necrosis Factor-alpha (TNF-α-Induced) Aquaporin-2 (AQP2) Expression in Renal Medullary Collecting Duct Cells Through Inhibiting the NF-κB Pathway

Abstract: BackgroundAquaporin-2 (AQP2) plays a major role in water reabsorption in the renal collecting duct, and is involved in a variety of renal disease. Recent studies have indicate that sirtuin1 (SIRT1) exerts renoprotective properties against kidney diseases. This study aimed to determine the potential role of SIRT1 in AQP2 expression induced by tumor necrosis factor-alpha (TNF-α) and to disclose the underlying mechanism in renal inner medullary collecting duct (IMCD) cells.Material/MethodsQuantitative real-time P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
3
11
0
2
Order By: Relevance
“…In addition, NF‐κB regulation of ICAM‐1 positively correlates with nephropathy by influencing mesangial cell proliferation . Moreover, NF‐κB participates to iNOS accumulation and, together with CREB, regulates AQP2 gene transcription . Whether UPARANT‐induced inhibition of HIF‐1α accumulation ameliorates kidney disease remains unclear as to some extent the activation of HIF‐1, but not its inhibition, seems to exert a beneficial role in the progression of DN .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, NF‐κB regulation of ICAM‐1 positively correlates with nephropathy by influencing mesangial cell proliferation . Moreover, NF‐κB participates to iNOS accumulation and, together with CREB, regulates AQP2 gene transcription . Whether UPARANT‐induced inhibition of HIF‐1α accumulation ameliorates kidney disease remains unclear as to some extent the activation of HIF‐1, but not its inhibition, seems to exert a beneficial role in the progression of DN .…”
Section: Discussionmentioning
confidence: 99%
“…58 Moreover, NF-κB participates to iNOS accumulation 59 and, together with CREB, regulates AQP2 gene transcription. 60 Whether UPARANT-induced inhibition of HIF-1α accumulation ameliorates kidney disease remains unclear as to some extent the activation of HIF-1, but not its inhibition, seems to exert a beneficial role in the progression of DN. 61 Suppression of inflammatory processes and ameliorated renal fibrosis results in recovered renal morphology as shown here by the reduction of glomerular hypertrophy and mesangial area increase.…”
Section: Recovery Of Kidney Lesionsmentioning
confidence: 99%
“…Енергетична депривація також збільшує вміст НАД + , що в свою чергу, призводить до активації НАД + -залежної дезацетилазної активності SIRT1. Активовані AMПK і SIRT1 через фосфорилю-вання і деацетилювання активізують PGC-1α, що, в свою чергу, індукує мітохондріальний біогенез і окиснення жирних кислот (рис.3) [1,6,21,[35][36][37][38][39]. Також було показано, що SIRT3 активує такі центральні регулятори циклу трикарбонових кислот, як глутаматде-гідрогенази й ізоцитратдегідрогенази.…”
Section: вплив сиртуїнів на метаболізмunclassified
“…Амілоїди в клітинах людей, які страждають на хворобу Альцгеймера, підсилюють ацетилювання RELA-субодиниці в мікроглії мозку, акти-вуючи NF-κB. При цьому SIRT1 деацетилює NF-κB, захищаючи таким чином нейрони [15,38,51].…”
Section: вплив сиртуїнів на метаболізмunclassified
“…For example, landmark studies by Brenner et al identified the activity of the renin-angiotensin system as a key player in the loss of GFR, and consequently, agents that block the system have successfully been introduced in clinical practice. 12,13 Clusterin (CLU) is discussed as molecule exerting its renoprotective properties by counteracting hypoxia/ischaemia-mediated injury via activation of prosurvival autophagy. 7 Research also identified acute kidney injury (AKI) as risk factor for the development of CKD, which also affects injury and repair mechanisms.…”
Section: Introductionmentioning
confidence: 99%